Sulfasalazine: a potent and specific inhibitor of nuclear factor kappa B. - Wahl, C (1998)
Transcription factors of the NF-kappaB/Rel family are critical for inducible expression of multiple genes involved in inflammatory responses. Sulfasalazine and its salicylate moiety 5-aminosalicylic acid are among the most effective agents for treating inflammatory bowel disease and rheumatoid arthritis. However, the mode of action of these drugs remains unclear. Here we provide evidence that the transcription factor NF-kappaB is a target of sulfasalazine-mediated immunosuppression. Treatment of SW620 colon cells with sulfasalazine inhibited TNFalpha-, LPS-, or phorbol ester- induced NF-kappaB activation. NF-kappaB-dependent transcription was inhibited by sulfasalazine at micro- to millimolar concentrations. In contrast, 5-aminosalicylic acid or sulfapyridine did not block NF-kappaB activation at all doses tested. TNFalpha-induced nuclear translocation of NF-kappaB was prevented by sulfasalazine through inhibition of IkappaBalpha degradation. When blocking proteasome-mediated degradation of IkappaBalpha, we could demonstrate that sulfasalazine interfered with IkappaBalpha phosphorylation, suggesting a direct effect on an IkappaBalpha kinase or on an upstream signal. Inhibition of NF-kappaB activation seems to be specific since other DNA-binding activities such as AP1 were not affected. These results demonstrate that sulfasalazine is a potent and specific inhibitor of NF-kappaB activation, and thus may explain some of the known biological properties of sulfasalazine.